PEMANFAATAN ARANG BIJI TERUNG BELANDA SEBAGAI PEWARNAAN ALTERNATIF KAPSUL BAKTERI - Bastian Bastian; Rossa Veronneca; Devi Apriani; Anggie Natalia (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Capsule staining is a technique used to determine whether a bacteria has a capsule in its body. The capsule is a polymer layer found outside the cell wall. Culture techniques can be used to identify Klebsiella pneumonia bacteria. The aim of this research is to prove that Dutch eggplant seed charcoal can be used as an alternative reagent for capsule coloring. This research includes collecting tamarillo eggplant, scorching tamarillo seeds to make charcoal, grinding the charcoal from tamarillo seeds, making MCA media, planting Klebsiella pneumonia bacteria on the media, making a coloring solution from tamarillo seed charcoal with the addition of 4N NaOH, observing bacterial capsules microscopically . Next, to see the bacterial capsules, staining was carried out using tamarillo seed charcoal dye and nigrosin ink dye / India ink as a comparison. The quality of capsule coloring from Dutch eggplant seed charcoal is 62.5% and nigrosin ink / India ink is 75%. The results of the research show that the comparison between tamarillo seed charcoal dye and nigrosin ink / India ink as a comparison is only 12.5 so that the alternative tamarillo seed charcoal dye can be used as a substitute for capsule dye